Two new species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Cameron’s Highlands, Peninsular Malaysia, with keys to 21 species of the Simulium asakoae species-group - Takaoka, H.; Sofian-Azirun, M.; Ya’cob, Z.; Hashim, R. (Zootaxa, 2014)
Two new black fly species, Simulium (Gomphostilbia) brinchangense and S. (G.) tanahrataense, are described on the basis of reared adult females, males, pupae and larvae from Cameron’s Highlands, Peninsular Malaysia. These new species are assigned to the asakoae species-group within Simulium (Gomphostilbia) and taxonomic notes are given to distinguish each new species from six known species in Malaysia. Revised keys to identify all 21 species including 13 species from other countries are provided for females, males, pupae and mature larvae. The species diversity of the asakoae species-group in Cameron’s Highlands is briefly noted.